MODERN OPPORTUNITIES FOR AIR SAFETY MANAGEMENT - Alexeiev, Oleh; Palamarchyuk, Victor; Pechevystyi, Ruslan; Karapetian, Serob (Proceedings of National Aviation University (archive), 2019)
The article describes the process of the basic elements of SMS, which is a security policy, through a radical change in industrial relations and the creation of "non-punitive" production environment, and defines the attitude to the experts in their erroneous actions, as well as the introduction of a system of voluntary notification of personnel about dangerous factors (risk factors), errors and incidents. The basis for the creation and reliable functioning of SMS is the formation of modern professional and corporate culture in the airline. An important part of it is a positive safety culture. All this should allow us to reach an acceptable level of aviation safety.